Background music tempo effects on food evaluations and purchase intentions. (November 2021) - Pantoja, Felipe; Borges, Adilson
Abstract: This article is a report of results of three studies investigating effects of fast versus slow background musical tempo on physiology, cognition, and emotions. Two pilot studies first measure consumer perceptions of tempo. In Studies 1 and 2, participants view a short video restaurant advertisement featuring fast or slow background music along with illustrations of food items. Results indicate that fast music is more effective than slow music for evoking positive taste expectations and purchase intentions. Study 3 shows that the effects observed in Studies 1 and 2 occur because fast music enhances self-reported arousal levels that then lead to enhanced moods, taste expectations, and purchase intentions. Theoretical implications regarding effects of music on emotional responses are discussed, as are practical managerial implications for using fast music as a persuasive technique. Highlights: Auditory stimuli influence consumers' reactions to food items. Faster (vs. slow) music tempo enhances food's perceived taste and purchase intentions. The effect of music tempo on food's perceived taste and purchase intentions is mediated by affection. Increases in arousal and mood serially mediate the positive effect of faster music on consumers' reaction to food items.